Odpowiedzi

Najlepsza Odpowiedź!
2010-03-03T16:21:07+01:00
A]6(x-4)-2=6x-24-2=6x-26
b]2(x+1)-3(x-1)=2x+2-3x+3=-x+5
c]-3(y-2)+4(y+2)=-3y+6+4y+8=y+14
d]5(x-y-1)-4(x+2)=5x-5y-5-4x-8=x-5y-13
1 4 1
2010-03-03T16:23:18+01:00
6(x-4)-2=6x-24-2=6x+26

2(x+1)-3(x-1)=2x+2-3x+3=x+5

-3(y-2)+4(y+2)= 3y+6+4y+8=7y+14

5(x-y-1)-4(x+2)=5x-5y-5-4x-8=x-5y-13

1 1 1
2010-03-03T16:27:23+01:00
A) 6(x-4)-2
6x-24-2
6x-26
b) 2(x+1)-3(x-1)
2x+2-3x+3
5x+5
c) -3(y-2)+4(y+2)
-3y+6+4y+8
-y+14
d) 5(x-y-1)-4(x+2)
5x-5y-5-4x-8
x-5y-13
1 2 1